ANALISIS PROSEDUR PEMBIAYAAN PRODUK CICIL EMAS BSI DALAM UPAYA MENINGKATKAN NASABAH PADA BANK SYARIAH INDONESIA KC BOJONEGORO - Rahayu Ningsih, Putri; Rahman, Taufiqur (Universitas Muhammadiyah Surabaya, 2023)
This research aims to determine the financing procedures for BSI gold installment products to increase financing customers for Bank Syariah Indonesia KC Bojonegoro. The Gold Installment Product is a financing product provided by BSI. However, the BSI gold installment product is not yet known to the public, this is indicated by the low number of financing customers at BSI KC Bojonegoro. The low number of BSI gold installment financing customers is due to a lack of public literacy regarding procedures for financing gold installment products. This research uses a qualitative descriptive research method. The data collection and analysis methods used are primary data in the form of observations and interviews, as well as secondary data in the form of journals, articles, books, and mass media related to research. The data analysis technique in this research is Miles and Huberman analysis. Covers four main things, namely data collection, data reduction, data presentation, and drawing conclusions or verification. The results of the discussion show that: The procedures for financing gold installment products at BSI KC Bojonegoro have been implemented by the provisions set by the BSI head office. The development of the number of gold installment customers at BSI KC Bojonegoro is said to be good and continues to increase every year. This development cannot be separated from the efforts made by BSI KC Bojonegoro. For this reason, the gold installment product has succeeded in increasing BSI KC Bojonegoro financing customers.